Exposure to acute stress affects the retrieval of out-group related bias in healthy men. (September 2021) - Pan, D.N.; Wolf, O.T.; Merz, C.J.
Abstract : Background: Individuals have a tendency to show enhanced vigilance to groups of which they themselves are not a member. Stress can up-regulate hypervigilance towards threatening stimuli and was shown to promote the reinstatement of out-group-related biases in a previous study conducted in women only. Methods: The current study examines how exposure to acute stress affects the retrieval of out-group related biases in male participants using a two-day paradigm, in which forty-four Caucasian participants acquired and extinguished fear associations for both in-group (Caucasian) and out-group (Moroccan) faces via a typical differential fear conditioning paradigm (Day1), and exposure to stress (SECPT) or control condition preceded the retrieval test (Day 2). Results: Men showed a specific out-group related bias at the beginning of extinction training indexed by higher SCRs towards out-group faces, especially out-group CS - (t(39)=2.71, p=.010, d=0.87); While stress can lead to a relapse of this extinguished out-group bias: the stress group showed higher SCRs towards out-group faces during retrieval compared to the control (F(1, 38)=5.75, p=0.022) and the bias index was negatively related to post-stress cardiovascular recovery. Conclusion: Stress can be severe as a potential risk factor to stimulate social racial prejudice recurrent in conditioning paradigm, along with potential modulation role of sex difference.